Tutoring Based Classroom Management Off-Task Behavioral Solutions - Widiastuti, Haning Tri (EPIK: Edukasi Penerapan Ilmu Konseling, 2022)
Off-task behavior is behavior that disrupts the learning process that often appears in the classroom. The phenomenon of off-task behavior also occurs in elementary schools which is the background for this research. The focus of attention in this study is to reduce the off-task behavior that exists in these elementary schools through guidance-based classroom management. The purpose of this study was to determine the effect of guidance-based classroom management in reducing off-task behavior. The research was conducted using a form of collaborative action research, which means that researchers and teachers collaborate in conducting guidance-based classroom management. The research data were obtained quantitatively using instruments developed by the researchers which then became the pre-test and post-test in this study. From research conducted on grade 3 elementary school students, showing a decrease in the value of the subject's off-task behavior, it can be concluded that guidance-based classroom management has an effect on students' off-task behavior.